‘DENTAL AGE FROM ERUPTION OF 3RD MOLAR AND COMPARISON WITH THE CHRONOLOGICAL AGE AMONG LIBYAN’ (Journal of Forensic Medicine & Toxicology, 2012)
The aim of the present investigation was to reconstruct the chronological age bases on third molar eruption evaluated by clinical examination. The cases were assembled from the school and university of Libyan origin between 15 and 25 years of age. A strong agreement was found between eruptions time of third molar and chronological age. The statistical analysis revealed that earliest third molar eruption was in the female at 16 year which has completed at 24 years in both the sexes. It also erupted earlier in lower jaw than upper jaw in both the sexes. The spaces for third molar also appear earliest in female at 15 year of age with early preponderance in lower jaw. This study has proved that teeth eruption is highly variable and an independent process to be followed, unrelated to other anthropometric measurements.
Keywords: Dental age estimation; Third molar; chronological age; Forensic odontology